Mirzai, Parvin - (:unkn) unknown (My University, 2026)
Parvin Farhad Mirzai received her first Bachelor’s degree in European Studies (English Language) from the Azerbaijan University of Languages in 2007. In 2015, she obtained a second Bachelor’s degree in Marketing from the Azerbaijan University of Architecture and Construction (AzUAC). In 2021, she completed her Master’s degree in Economic Theory at the National Transport University of Ukraine. Since 2009, she has been working at AzUAC. From 2009 to 2023, she served as a Senior Laboratory Assistant at the Department of Economic Theory and Marketing. Since 2022, she has been working as an Assistant Lecturer at the same department. Her research interests focus on economic theory and marketing. Her scientific work has been published in Azerbaijan, and one of her papers has been accepted for publication in a Scopus-indexed journal.